Flat White or With A Round Character? : New light on stone funerary slabs and orbs from south Sweden - Back Danielsson, Ing-Marie ; 0000-0003-1549-582X (World Archaeology, 2026)
Stone funerary orbs with carved ornamentation, along with similarly decorated stones, but in the form of slabs, are a distinctive yet underexplored category of archaeological objects from Late Iron Age Sweden. These carved stones are originally found in burial contexts from the Migration Period (c. 400–550 CE) and at times early Vendel Period (c. 550–800 CE). In later centuries, they are known to have been removed from their original context, and re-used for other purposes. This paper discusses stone funerary orbs and slabs from the Mälar Valley, south Sweden, and sheds light on their different object itineraries throughout time. In doing so, it focusses on the making of their ornamentation, and its (desired) affects and effects, as well as the possible qualities that were associated with the stone itself (e.g. form, colour, descent) and how these aspects may have played pivotal roles in their removal from burial contexts to new ontological realms.
Keywords: Stone funerary orb; stone funerary slab; Iron Age; Sweden; object itinerary; societal transitions